Ventricular assist devices for treatment of acute heart failure and chronic heart failure. Issue 14 (6th May 2015) - Kirkpatrick, James N; Wieselthaler, Georg; Strueber, Martin; St John Sutton, Martin G; Rame, J Eduardo
Abstract : Despite therapeutic advances that improve longevity and quality of life, heart failure (HF) remains a relentless disease. At the end stage of HF, patients may become eligible for mechanical circulatory support (MCS) for the indications of stabilising acute cardiogenic shock or for chronic HF management. MCS use is growing rapidly in the USA and some countries of the European Union, especially in transplant-ineligible patients. In others, it remains largely a tool to stabilise patients until heart transplant. MCS comprises a heterogeneous group of temporary and durable devices which augment or replace the pumping function of one or both ventricles, with postimplant 2 year survival rivalling that of transplant in selected, lower-risk patients. In transplant-eligible and non-transplant-eligible patients, improvement in end-organ perfusion, functional capacity and quality of life have been noted. Even for optimal candidates, however, there are a host of potential complications that require constant vigilance of a coordinated care team. Recently, there has been official recognition of the importance of palliative care expertise in advance care planning preimplant and management of patients with ventricular assist devices at the end of their lives.